Natural resource investment and Africa?s development - Botchway, Francis (Cheltenham Edward Elgar, 2011)
This well-researched book covers a wide spectrum of important issues that are central to investment in natural resources and ultimately, economic development of Africa.
Includes bibliographical references and index
Keywords: Investments, Foreign -Africa.